Community Engagement with Wildlife Conservation in Japan: A Case Study of an Endangered Bird, the Okinawa Rail (Hypotaenidia okinawae) - Madeleine Sbeghen (New Voices in Japanese Studies, 2017)
As host of the 2010 Nagoya Biodiversity Summit, Japan reaffirmed its efforts to conserve biodiversity for future generations. Rebuilding relationships with nature and strengthening conservation education are key priorities of Japan’s biodiversity conservation agenda to improve outcomes for threatened species and local communities. This paper examines community engagement with the critically endangered Okinawa Rail (Hypotaenidia okinawae), an endemic bird of the Yanbaru forests of northern Okinawa, with reference to the conservation context in Japan. Since discovery of the Okinawa Rail in 1981, communities in Yanbaru have developed a strong relationship with this species, recognising it as an important symbol of regional cultural identity and as a unique ecological asset that attracts visitors and underpins community events. This has translated into investment by government and community stakeholders in conservation education facilities and public awareness campaigns for the Okinawa Rail in Yanbaru. To improve the long-term value of facilities to support science-based conservation efforts in this Japanese context, it could be advantageous to increase opportunities for social learning that incorporate both educational and conservation goals, and which encourage stakeholder partnerships. The complex socio-economic and political context in Okinawa, and the significant impact human activities have on the Okinawa Rail population, also highlight the importance of community cooperation in conservation activities and reinforce the value of interdisciplinary approaches that negotiate cross-cultural differences in biodiversity conservation.